2020
DOI: 10.3390/s20030819
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Sensing of Caffeine in Tea Beverages with 3,5-diaminobenzoic Acid

Abstract: A rapid, selective and sensitive method for the detection of caffeine in tea infusion and tea beverages are proposed by using 3,5-diaminobenzoic acid as a fluorescent probe. The 3,5-diaminobenzoic acid emits strong fluorescence around 410 nm under the excitation of light at 280 nm. Both the molecular electrostatic potential analysis and fluorescent lifetime measurement proved that the existence of caffeine can quench the fluorescence of 3,5-diaminobenzoic acid. Under the optimal experimental parameters, the 3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Therefore, efforts have been made to develop analytical methods to detect caffeine. Aside from analytical instrumentation such as mass spectrometry coupled with high-performance liquid chromatography (HPLC), a few sensors including molecular fluorescent probes, immunoassays, nanomaterials such as graphene oxide and lanthanide-containing materials, and molecularly imprinted polymers have been reported. Sensors are attractive since they allow cost-effective and on-site detection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, efforts have been made to develop analytical methods to detect caffeine. Aside from analytical instrumentation such as mass spectrometry coupled with high-performance liquid chromatography (HPLC), a few sensors including molecular fluorescent probes, immunoassays, nanomaterials such as graphene oxide and lanthanide-containing materials, and molecularly imprinted polymers have been reported. Sensors are attractive since they allow cost-effective and on-site detection.…”
Section: Introductionmentioning
confidence: 99%
“…5 Therefore, these three components, namely CFN, THN and GCL, can be dangerous if present in food and medicines simultaneously in excess amounts, and hence the detection of CFN, THN and GCL is essential for the safe use of medicines, food products and beverages. To date, various analytical techniques such as gas chromatography-mass spectrometry, 6 gas chromatography, 7 fluorescence, 8,9 high-performance liquid chromatography, 5,10 surface-enhanced Raman spectroscopy, 11,12 and colorimetric, 13,14 TLC-densitometric, 15 kinetic spectrophotometric 16 and electrochemical sensing have been used for the sensing of CFN, THN and GCL. However, these approaches, except the electrochemical method involve complicated operation procedures, are time-consuming and have low sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine's ability to attach to receptors allows it to prevent the release of certain neurotransmitters, which have sedative and anticonvulsant properties (Chen et al 2021). The European Committee Authorities of Food Science has suggested that people should not consume more than 400 mg of CAF per day (Du et al 2020). Since adenosine and CAF have similar chemical structures, when adenosine receptors attach to CAF molecules, the effects of adenosine on those receptors are lessened and blocked, preventing adenosine from inducing sleepiness (Carolina Torres et al 2014).…”
Section: Introductionmentioning
confidence: 99%